Proposta de melhoria no processo de picking: estudo de caso em um centro de distribuição farmacêutica na cidade de Manaus/AM - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
This research studies the picking process at a pharmaceutical distribution company, located in the city of Manaus/AM, the largest urban center in the Brazilian Amazon where, due to its geographical characteristics and the need to efficiently serve the capital and the small drugstores located in small communities, it has different characteristics and specificities from other places on the planet. The definition and analysis of performance indicators for a Distribution Centre are topics that are discussed, improved and recurrent, and the performance of the Picking process is one of the main indicators, especially for the case studied, where the company serves. Most of the customers are small businesses that don't have adequate space in their units for storing products and working capital that can be committed to stock. This is the type of customer that predominates in the city of Manaus and the state of Amazonas. This characteristic requires distribution to sort and deliver small quantities with great frequency, thus avoiding a shortage of pharmaceutical products. The aim of this study is to identify the factors that directly influence the drop in the service level of the picking routines. In order to achieve this objective, the quality tool Value Stream Mapping was used, and at the end strategies were presented for solving the problems identified in the analysis process. In order to carry out the research during the methodological process, data collection included direct observation of the operation, documentary records from the quality area, such as stock control spreadsheets and performance reports by operators, as well as the use of closed questionnaires for customers and employees. The results and conclusions obtained in relation to the factors that directly influence a drop in the level of service of the picking routines are 05: picking items by stations, thin stock (retail), order consolidation and closing, printing invoices, printing orders, distribution of orders by picking zones. As for defining a methodology for measuring the service level of the picking routines, according to our study, the quality tool that best applies is the VSM. With regard to the opportunities for improvement identified in the processes under analysis, we highlight 05 Improvement in the process of replenishing allocations, Improvement in the addressing of the Flow-rack, Improvement in the information technology infrastructure, Improvement in the technology in the automation process.
Proposal for improvement in the picking process: case study in a pharmaceutical distribution center in the city of Manaus/AM
Keywords: Distribuição de mercadorias - Amazonas; Logística empresarial; Produção enxuta; ENGENHARIAS: ENGENHARIA DE PRODUCAO: GERENCIA DE PRODUCAO: PLANEJAMENTO, PROJETO E CONTROLE DE SISTEMAS DE PRODUCAO; Armazém; Processo de picking; Distribuição farmacêutica; Mapeamento do fluxo de valor; Lean manufacturing; Warehouse; Picking process; Pharmaceutical distribution; Value stream mapping